2018
DOI: 10.1371/journal.pone.0198243
|View full text |Cite
|
Sign up to set email alerts
|

Leaf traits drive plant diversity effects on litter decomposition and FPOM production in streams

Abstract: Biodiversity loss in riparian forests has the potential to alter rates of leaf litter decomposition in stream ecosystems. However, studies have reported the full range of positive, negative and no effects of plant diversity loss on decomposition, and there is currently no explanation for such inconsistent results. Furthermore, it is uncertain whether plant diversity loss affects other ecological processes related to decomposition, such as fine particulate organic matter production or detritivore growth, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 40 publications
(57 reference statements)
4
25
2
Order By: Relevance
“…Freshly fallen senesced leaf litter of A. glutinosa, S. cinerea and F. sylvatica were collected every second day, whereas leaf litter of I. aquifolium was obtained by cutting branches in the field and simulating senescence by air-drying and allowing laves to fall off from the branches in the laboratory during a period of three to four weeks (Handa et al, 2014;Makkonen et al, 2012). López-Rojo et al (2018) found that the N concentration of I. aquifolium leaves collected from branches did not significantly differ from senescent leaves which are shed in the field. After collection, the litter was dried at 40°C for one…”
Section: Study Sites and Plant Materialsmentioning
confidence: 99%
“…Freshly fallen senesced leaf litter of A. glutinosa, S. cinerea and F. sylvatica were collected every second day, whereas leaf litter of I. aquifolium was obtained by cutting branches in the field and simulating senescence by air-drying and allowing laves to fall off from the branches in the laboratory during a period of three to four weeks (Handa et al, 2014;Makkonen et al, 2012). López-Rojo et al (2018) found that the N concentration of I. aquifolium leaves collected from branches did not significantly differ from senescent leaves which are shed in the field. After collection, the litter was dried at 40°C for one…”
Section: Study Sites and Plant Materialsmentioning
confidence: 99%
“…We used leaf litter from 9 tree species belonging to 3 families (Betulaceae, Salicaceae and Fagaceae), which were introduced in microcosms (with and without detritivores) as monocultures (SR = 1) or mixtures (SR = 3) with either low PD (3 species from the same family) or high PD (3 species from 3 different families). The above processes were quantified after 6 weeks, and the following hypotheses were examined: (1) plant SR enhances all studied processes (i.e., they have greater values in mixtures than in monocultures) 15,28 , mostly due to complementarity effects 29 ; (2) the difference between monocultures and mixtures is greater for high-PD than for low-PD mixtures; and (3) all the above patterns are more marked in the presence of detritivores, which often are key drivers of biodiversity-ecosystem process relationships [30][31][32] .…”
mentioning
confidence: 99%
“…These intermediate leaf proportions had the effect of composition of leaf litter mixtures, which may determine decomposition (Rezende et al, 2016(Rezende et al, , 2017. Different leaf species have different chemical characteristics (Graça et al, 2015); such interspecific differences have substantial effects on leaf breakdown rates (López-Rojo et al, 2018). In a mixture of labile and refractory litter species, shredders focused more on the most labile litter species (Swan & Palmer, 2006).…”
Section: Discussionmentioning
confidence: 99%